Pengaruh Kinerja Keuangan Perusahaan terhadap Kinerja Sosial Perusahaan - Pasaribu, Riana Elizabet Tiurma (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2016)
Social performance is an activity undertaken by the company as a form of social responsibility. One of the factors that affect the social performance of the company is financial performance. The financial performance of the company can be seen from the financial ratios. Financial ratios are considered often seen by investors is profitability and leverage ratios. This study aimed to examine the effect of financial performance which is proxied by ROA, ROE, EPS and DER towards corporate social performance. Samples of this research is company property, real estate and construction of 48 companies listed on the Indonesia Stock Exchange. Methods of data collection using the methods of literary study. Data analysis techniques in this study included descriptive statistics, test data quality, classic assumption test, regression analysis, and analysis of different test using SPSS 17.0. The analysis showed that the ROA as a proxy of financial performance have significant positive effect on social performance in the period of 2012, but has no effect on the period of 2013.While ROE and EPS do not have a significant positive effect and DER variables do not have a significant negative effect on the performance of social enterprise in the period 2012 and 2013. For more see clearly the effect of the financial performance in each period, the researchers also did a different test. Different test results showed that there were differences in financial performance in the period 2012 and 2013.